Sustaining Change : Leadership That Works. - Rowland, Deborah (John Wiley & Sons, 2008)
This is a book destined for leaders who wish to implement change more intelligently and effortlessly. Drawing on a combination of rigorous research and extensive organizational experience, the authors present a framework for leading change, Changing Leadership, that describes the specific leader practices they have found make the biggest difference between success and failure in implementing high magnitude change. In doing all of this, the leader works to make change happen in the day to day activity and conversations of the organization.